Plasma Rotavirus-specific IgA and Risk of Rotavirus Vaccine Failure in Infants in Malawi. (12th November 2021) - Pollock, Louisa; Bennett, Aisleen; Jere, Khuzwayo C; Mandolo, Jonathan; Dube, Queen; Bar-Zeev, Naor; Heyderman, Robert S; Cunliffe, Nigel A; Iturriza-Gomara, Miren
Abstract: Background: Rotavirus vaccine efficacy is reduced in low-income populations, but efforts to improve vaccine performance are limited by lack of clear correlates of protection. Although plasma rotavirus (RV)-specific immunoglobulin A (IgA) appears strongly associated with protection against rotavirus gastroenteritis in high-income countries, weaker association has been observed in low-income countries. We tested the hypothesis that lower RV-specific IgA is associated with rotavirus vaccine failure in Malawian infants. Methods: In a case-control study, we recruited infants presenting with severe rotavirus gastroenteritis following monovalent oral rotavirus vaccination (RV1 vaccine failures). Conditional logistic regression was used to determine the odds of rotavirus seronegativity (RV-specific IgA < 20 U/mL) in these cases compared 1:1 with age-matched, vaccinated, asymptomatic community controls. Plasma RV-specific IgA was determined by enzyme-linked immunosorbent assay for all participants at recruitment, and for cases at 10 days after symptom onset. Rotavirus infection and genotype were determined by antigen testing and reverse transcription-polymerase chain reaction, respectively. Results: In 116 age-matched pairs, infants with RV1 vaccine failure were more likely to be RV-specific IgA seronegative than controls: odds ratio, 3.1 (95% confidence interval [CI], 1.6–5.9), P =.001. In 60 infants with convalescent serology, 42/45 (93%; 95% CI. 81–98) infants seronegative at baseline became seropositive. Median rise in RV-specific IgA concentration following acute infection was 112.8 (interquartile range, 19.1–380.6)-fold. Conclusions: In this vaccinated population with high residual burden of rotavirus disease, RV1 vaccine failure was associated with lower RV-specific IgA, providing further evidence of RV-specific IgA as a marker of protection. Robust convalescent RV-specific IgA response in vaccine failures suggests differences in wild-type and vaccine-induced immunity, which informs future vaccine development. Abstract : In a case-control study of monovalent rotavirus vaccinated Malawian infants, low plasma rotavirus (RV)-specific immunoglobulin A (IgA) at presentation with gastroenteritis was strongly associated with clinical vaccine failure. Infants with vaccine failure nevertheless demonstrated a robust RV-specific IgA response to acute infection.